2016
DOI: 10.1158/2159-8290.cd-15-0510
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy with Immunomodulatory Anti-CD137 and Anti–PD-1 Monoclonal Antibodies Requires BATF3-Dependent Dendritic Cells

Abstract: Weak and ineffective antitumor cytotoxic T lymphocyte (CTL) responses can be rescued by immunomodulatory monoclonal antibodies (mAbs) targeting PD-1 or CD137. Using Batf3-/- mice, which are defective for cross-presentation of cell-associated antigens, we show that Batf3-dependent dendritic cells (DCs) are essential for the response to therapy with anti-CD137 or anti-PD-1 mAbs. Batf3-/- mice failed to prime an endogenous CTL-mediated immune response toward tumor-associated antigens, including neoantigens. As a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
324
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(349 citation statements)
references
References 29 publications
10
324
0
1
Order By: Relevance
“…We took advantage of two well-known immunogenic solid tumor models in mice, CT26 and MC38. These tumors are controlled by CD8 + T cells thus prone to respond to immunotherapy (14,17,22,23). Moreover, studies in mice have shown a link between mutational load of the tumor and clinical efficacy of immunotherapy (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We took advantage of two well-known immunogenic solid tumor models in mice, CT26 and MC38. These tumors are controlled by CD8 + T cells thus prone to respond to immunotherapy (14,17,22,23). Moreover, studies in mice have shown a link between mutational load of the tumor and clinical efficacy of immunotherapy (24).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor models, tumor inoculation in mice, and antitumor treatments CT26 and MC38 are two immunogenic tumor models controlled by CD8 + T cells and known to respond to immune checkpoint blockers such as anti-PD-1 (14)(15)(16)(17) Mouse single cell preparation from spleen, lymph node, lung, bone marrow, and tumors Spleen and lymph nodes. Single cells were obtained after mechanical disruption, and RBCs were lysed using ACK lysing buffer (spleen).…”
Section: In Vivo Bioactivity Of Rli In Micementioning
confidence: 99%
“…In theory, this might lead to a higher response rate to immune checkpoint inhibition. Furthermore, the unique capability of DCs to cross-present antigens helps to induce an immune response to a wide variety of tumor antigens when applied in conjunction with immune checkpoint inhibitors (88). The timing of the combination may be of crucial importance for its efficacy.…”
Section: Combination With Immune Checkpoint Inhibitors: the Ideal Commentioning
confidence: 99%
“…[8][9][10]57 To improve clinical efficacy, it is probably necessary to combine vaccination with checkpoint modulators or other strategies countering immunological tolerance. 6,25,52,[66][67][68][69][70][71] As a combination strategy will increase the risk of side effects, it is encouraging that our vaccine study indicated low toxicity, even after long-term follow-up. One may further note that the longterm survivors (M22 and M109) responded well to treatment with ipilimumab.…”
Section: Discussionmentioning
confidence: 82%